(untitled) (Research, Society and Development, 2021)
The article reports the reception practices to a person with a suspected case of leprosy and the educational activities developed among the community during the practical activities of nursing students in a primary care clinic located in a municipality of the State of Rio de Janeiro (RJ), in october 2019. In view of the leprosy’s circumstances in Brazil, and the reception of patient A. it was built a reflection about the vulnerabilities and the lack of information which increase the stigma related to worsening of the condition and decrease the access to diagnostic and timely treatment. In this perspective, from the practical activity, it was experienced the expansion of theoretical and practical knowledge of the students about the nurse’s role in facing leprosy as a public health issue. The health education action focused on identifying, treating and fighting against the stigma implemented through the light technology techniques with the population provided approximation and open dialogue regarding leprosy. Therefore, it is expected to encourage new extension projects and practical activities aiming at the nursing development, studies and sensibilization of students, professors as well as the general population regarding the theme.